A case of successful laser coagulation in pediatric ophthalmology: a patient with the optic disc pit complicated by serous neuroepithelial detachment - Shevchenko, I.I. (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Optic disk pit has been considered as coloboma located, as a rule, near temporal part of the optic disc. Central serous retinal detachment develops in 50 % of patients. The purpose of the present study was to show practically the possibility to use laser coagulation as an entire method for treatment of optic disc pit complicated by serous neuroepithelial detachment in children. Material and Methods. A patient, 4 y/o, with Jensen’s retinochoroiditis juxtapapillaris, optic disc pit and serous neuroepithelial detachment was followed up. The patient was performed 532 nm laser, optical coherent tomography, visiometry, biomicroscopy, ophthalmoscopy and immunology research. Results. Visual acuity increased from 0.08 to 0.5 after treatment. Neuroepithelial attachment was achieved with residual detachment up to 40 µm. Conclusions. This case demonstrates that laser coagulation of the retina can be used as a separate and minimally invasive method of treatment for patients with optic disk pits complicated by serous neuroepithelial detachment in pediatric ophthalmology.